Agilent Technologies Technical Solutions as an Effective Tool for Determination and Monitoring of Foodstuff Parameters - Ruzhitskaya, K.V.; Duzhak, A.A. (Science and Innovation, 2024)
A brief overview of some product lines manufactured by Agilent Technologies (California, USA) and possible areas of their application are given. The equipment is designed to meet the individual needs and peculiarities of different industries. The Agilent Technologies solutions are widely used in the field of agriculture and food production.